Denoising of ECG Using UWT and Diagnosis of Diseases - George, Eldho; Rajmohan, M. (Journal of Advanced Research in Medical and Health Science (ISSN 2208-2425), 2015)
This paper presents a new approach to eliminate the noise found in ECG signals due to artifacts and cardiac rhythm. This work is carried out using the Undecimated Wavelet Transform (UWT). The signals were acquired using an MATLAB SIMULATION of bioelectrical The ECG signals are obtained through the implant of electrodes connected to a channel of the front- end board. The cardiac rhythm is then obtained using an optic dactilar sensor connected to an independent channel of the ECG signal. In order to get a better identification of the acquired signal the Wavelet filter D6 (Daubechies) was chosen, primarily because its scaling function is closely related to the shape of the ECG, fitting very well with the applications constraints The processed signals were further analyzed using SIMULATION using MATLAB. The application to denoise the ECG signals was developed by MATLAB 2008Rb and is capable of graphically representing the data before and after it’s processed.